Everyday Discourses of Menstruation Cultural and Social Perspectives - Newton, Victoria Louise; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
'This book offers an original contribution to a number of fields including anthropology, cultural studies, sociology and gender studies. Social norms, beliefs and practices around menstruation remain a significantly underresearched and under-theorised experience and as such this book makes a valuable and timely contribution.' - Kay Inckle, London School of Economics and Political Science, UK Menstruation is a topic which is both everyday and sensitive. From Leviticus to Pliny, to twentieth-century debates around 'menotoxin', to advertising and 'having the painters in', Victoria Newton's book offers a lively and innovative exploration of the social and cultural dimensions of menstruation. Through in-depth interviews with men and women, the book explores the many different ways in which this sensitive topic is spoken about in British culture. Looking specifically at euphemism, jokes, popular knowledge, everyday experience and folklore, the book provides original insights into the different discourses acting on the menstruating body and encourages debate about how these help to shape our everyday attitudes towards menstruation. Victoria Newton is a research associate in the Faculty of Health and Social Care at The Open University, UK. She is an interdisciplinary researcher with interests in sexual and reproductive health, the articulation of sensitive subjects in the everyday, and informal knowledge and belief concerning the body. .
Foreword; Richard Jenkins -- Chapter 1. The 'Folklore of Menstruation': Researching Vernacular Knowledge and Everyday Experience -- Chapter 2. Periods: Historical and Cultural Interpretations of Menstruation -- Chapter 3. Positioning Periods in Context: Contemporary Discourses and Dilemmas -- Chapter 4. On the Blob: Young Adulthood and Menstrual Lore -- Chapter 5. Managing Menstruation: The Menarche and Status Passage -- Chapter 6. Talking about My Menstruation: A Generational Comparison -- Chapter 7. The Curse: Popular Histories and Cultural Knowledge -- Chapter 8. 'Auntie's Come to Tea': Menstrual Euphemism -- Chapter 9. Mentioning the Unmentionable: 'Only Joking...' -- Chapter 10. Closed for Maintenance: Backstage spaces, and Selling Shame -- Chapter 11. Conclusions: Keep Bleeding.
Keywords: Human body-Social aspects; Sociology; Feminist anthropology